2023
DOI: 10.1101/2023.05.21.23290300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lack of univariate, clinically-relevant biomarkers of autism in resting state EEG: a study of 776 participants

Abstract: Mental health conditions are difficult to diagnose, requiring expert clinicians and subjective judgements. There has been interest in finding quantitative biomarkers using resting state electroencephalogram (EEG) data. Here, we focus on resting state EEG biomarkers of autism. Although many previous reports have pointed to differences between autistic and neurotypical participants, results have often failed to replicate and sample sizes have typically been small. Taking a big-data, open-science approach, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…Contrary to work implicating involving beta waveform shape in Parkinson’s disease (Cole, van der Meij, et al, 2017), we found no significant differences in alpha-band rhythm features for either of two prominent neurodevelopmental disorders. This is consistent with recent work from Dede et al, 2023 that failed to find a single biomarker for ASD after extracting a high number of measures from resting-state EEG (in sensor space, including band-power and frequency measures) in a dataset of 776 individuals. There is large inter-individual variation in alpha-band rhythm features, but high internal consistency (Lopez et al, 2023), which hints at the fact that usage of longitudinal data (Gabard-Durnam et al, 2019) may be a promising approach to capture diagnosis-related information sufficiently.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to work implicating involving beta waveform shape in Parkinson’s disease (Cole, van der Meij, et al, 2017), we found no significant differences in alpha-band rhythm features for either of two prominent neurodevelopmental disorders. This is consistent with recent work from Dede et al, 2023 that failed to find a single biomarker for ASD after extracting a high number of measures from resting-state EEG (in sensor space, including band-power and frequency measures) in a dataset of 776 individuals. There is large inter-individual variation in alpha-band rhythm features, but high internal consistency (Lopez et al, 2023), which hints at the fact that usage of longitudinal data (Gabard-Durnam et al, 2019) may be a promising approach to capture diagnosis-related information sufficiently.…”
Section: Discussionsupporting
confidence: 91%